Settlement in the Bestansur Site Under the Light of Recent Excavations - Hawar Najmadin Hawas; Noaman Irahim Jumaa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
One of the effective and reliable methods to prove the life of human beings in the pre-history stage is excavation and inspection of archaeological sites. The results of such endeavors could help us understand the secrets of human beings in the past. Excavations have yielded significant results in the world and in the history of Kurdistan in particular. One of the results gained from excavation of Bestansur village is about human settlement in the village during pre-pottery Neolithic stage. The results show the styles of construction and primary of ways of agriculture, animal husbandry and how humans depended on these two processes as main resources of economy. It shows many aspects of life, particularly the belief of buried the dead in that stage.